Endocrine Aspects of Pain Pathophysiology: Focus on Adipose Tissue - Ozcan, Mete; Ayar, Ahmet (Karger, 2024)
Background: Multiple factors, including neurobiological, hormonal, psychological, and social/cultural norms, influence the manner in which individuals experience pain. Adipose tissue, once considered solely an energy storage site, has been recognized as a significant endocrine organ that produces and releases a range of hormones and cytokines. In recent years, research has highlighted the role of adipose tissue and its endocrine factors in the pathophysiology of pain. Summary: This narrative review aimed to provide a comprehensive overview of the current knowledge on the endocrine aspects of pain pathophysiology, with a specific focus on adipose tissue. We examine the role of adipokines released by adipose tissue, such as leptin, adiponectin, resistin, visfatin, asprosin in pain perception and response. We also explore the clinical implications of these findings, including the potential for personalized pain management based on endocrine factors and adipose tissue. Key Messages: Overall, given this background, this review intended to highlight the importance of understanding the endocrine aspects of pain pathophysiology, particularly focusing on the role of adipose tissue, in the development of chronic pain and adipokines. Better understanding the role of adipokines in pain modulation might have therapeutic implications by providing novel targets for addressing underlying mechanism rather than directly focusing on symptoms for chronic pain, particularly in obese individuals.
Keywords: Colony-Enhancing Factor; Necrosis-Factor-Alpha; Leptin Receptor; Skeletal-Muscle; Insulin-Resistance; Apelin/Apj System; Neuropathic Pain; Synovial-Fluid; Therapeutic Target; Metabolic Syndrome